Shock effects in the Willamette ungrouped iron meteorite. (13th November 2015) - Rubin, Alan E.; Breen, John P.; Wasson, John T.; Pitt, Darryl
Abstract: A slab of the Willamette ungrouped iron contains elongated troilite nodules (up to ~2 × 10 cm) that were crushed and penetrated by wedges of crushed metal during a major impact event. What makes this sample unique is the contrast between the large amount of shock damage and the very small (~1%) amounts of shock melting in the large troilite nodules. The postshock temperature was low, probably ≾960 °C. The Widmanstätten pattern has been largely obscured by an episode of postshock annealing that caused recrystallization of the kamacite. The shock and thermal history of Willamette includes (1) initial crystallization and formation of multicentimeter‐size troilite nodules from trapped melt, (2) impact‐induced melting of metal‐sulfide assemblages to form lobate taenite masses a few hundred micrometers in size, (3) impact‐crushing of the nodules and jamming of metal wedges into them, (4) simultaneous crushing of metal grains adjacent to sulfide throughout the meteorite, (5) postshock annealing causing minor recrystallization of metal and troilite, and (6) a late‐stage shock event (and additional annealing) producing Neumann lines in the kamacite.